Biodiversity of Plant Polysaccharide-Degrading Bacteria in Mangrove Ecosystem - Go Furusawa, (Tropical Life Sciences Research, 2019)
The mangrove ecosystem is the most productive environment and represent a rich biological diversity including microorganisms. Plant polysaccharides, such as cellulose, hemicellulose and pectin are significant carbon sources of the ecosystem. Bacteria play an important role in carbon cycle in the ecosystem as a decomposer. Based on culture-dependent methods, many plant polysaccharide-degrading bacteria were isolated from mangrove sediments. However, only four bacterial phyla were found in the isolates. In contrast, functional and taxonomic analysis of metagenomic datasets indicated that 10 to 12 bacterial phyla involve in hemicellulose degradation. A large number of anaerobic bacteria, such as the genera Clostridum, Dictyoglomus Marinitoga, Petrotoga, Thermotoga and Verrucomicrobia, were found among them. In addition, many hemicellulose degradation enzymes were found in the phylum Acidobacteria which are abundant and ubiquitous across soil environments. These results suggest that various kinds of bacteria including anaerobic bacteria contribute Plant polysaccharide degradation.